ERROR ANALYSIS OF EIGHTH-GRADE STUDENTS AT SMP N 6 PALU IN SOLVING AKM NUMERACY PROBLEMS VIEWED FROM A GENDER PERSPECTIVE - Juliartini, Ni Kadek; Mubarik, Mubarik; Sukayasa, Sukayasa; M, Bakri (Universitas Tanjungpura, 2025)
The purpose of this study is to describe the mistakes of male and female students in solving numeracy AKM problems based on Newman procedures. The method used in this study is a qualitative descriptive method. Some of the results obtained from this study are: (1) mistakes made by male students including comprehension errors occurred because students read the questions once quickly and did not know which ones to write because the questions were too long, process skill errors occurred because students were not careful in calculating multiplication and division operations, and encoding errors occurred because students were in a hurry to do the problems; (2) mistakes made by female students include comprehension errors occurring because students read the questions once and do not know which ones to write because the questions are too long, transformation errors occur because students do not know the formula for finding averages, process skills errors occur because students are not able to calculate correctly, and encoding errors occur because students are not careful in reading what is asked in the questions.(3) The most dominant mistake made by male and female students is comprehension error. This mistake occurs because students read the questions only once, making them unable to fully understand the information provided in the questions and not knowing which points to write down due to the questions being too lengthy.